2020
DOI: 10.1101/2020.09.28.316422
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Measuring effects of trainee professional development on research productivity: A cross-institutional meta-analysis

Abstract: PhD-trained scientists are essential contributors to the workforce in diverse employment sectors that include academia, industry, government, and non-profit organizations. Hence, best practices for training the future biomedical workforce are of national concern. Complementing coursework and laboratory research training, many institutions now offer professional training that enables career exploration and develops a broad set of skills critical to various career paths. The National Institutes of Health funded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
(22 reference statements)
1
4
0
Order By: Relevance
“…Results showed web 2.0 technologies positively and significantly mediate the relationship between research competences and research productivity, supporting H4. The previous research findings also confirmed the relationship between RC and RP through web 2.0 technologies [33] among vocational-health education students [90]. Similarly, results showed that research skills help enhance research productivity among vocational-health education students through web 2.0 technologies [91].…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Results showed web 2.0 technologies positively and significantly mediate the relationship between research competences and research productivity, supporting H4. The previous research findings also confirmed the relationship between RC and RP through web 2.0 technologies [33] among vocational-health education students [90]. Similarly, results showed that research skills help enhance research productivity among vocational-health education students through web 2.0 technologies [91].…”
Section: Discussionsupporting
confidence: 59%
“…Numerous studies in the field of medical science have emphasized the role of professional training and career exploration programs in building research competence. A recent study by [33] on doctoral students in the biomedical field highlighted that researchers invested in training and development, were more aware of their research competences, and observed productive outcomes in their research work and career. Research competences gained during postgraduate programs help vocational-health education students become expert researchers [9].…”
Section: Research Competences Influence the Research Productivitymentioning
confidence: 99%
“…In addition, some faculty stakeholders do not see the value of CPD activities and expressed some concern about the time their pre-and postdoctoral researchers dedicate to these activities. However, recent evidence-based research has shown that participation in internships, career development programming, K-12 outreach programs or IRACDA programs does not lead to increased time to degree or decreased productivity (Brandt et al, 2020;Gamse et al, 2010;Rybarczyk et al, 2011;Schnoes et al, 2018). Pre-and postdoctoral researchers, faculty-administrators and external partners all noted the value of flexible programming to encourage pre-and postdoctoral researcher engagement.…”
Section: Common Themesmentioning
confidence: 99%
“…Foremost among them is the faculty. Data from the BEST Consortium indicated that a large majority of faculty are supportive of career training for various careers and have recognized that pre-and postdoctoral researchers participating in CPD activities were happier and making timely progress toward degree completion -a fact that can be used to recruit additional internal stakeholder engagement from faculty (Brandt et al, 2020;Chatterjee et al, 2019;Watts et al, 2019). Faculty don't always believe they have the knowledge or resources to assist pre-and postdoctoral researchers whose career interests lie outside academia, although they largely support their career pursuits (Engelhardt & Alder, 2020;St.…”
Section: Internal Stakeholdersmentioning
confidence: 99%
“…Such opportunities include internships (temporary employment at a trainee level), job simulation (completing projects like those done by professionals but in a non-employment context), job shadowing (observing a professional in the workplace to learn about job expectations), and site visits (observational visits to a workplace) (Council of Canadian Acadmies, 2021;Edge & Munro, 2015;Wart et al, 2020). Experiential learning activities are associated with benefits for trainees including recognition of transferable skills (Sealey et al, 2020;Sinche et al, 2017; Developing an Industry Job Simulation Program 85 et al, 2019), confidence in choosing a career path (Schnoes et al, 2018;Sealey et al, 2020;Yung et al, 2019), facilitating the transition to employment (BioTalent Canada, 2020;Edge & Munro, 2015;Her et al, 2018;Sealey et al, 2020;Yung et al, 2019) and decreased likelihood of pursuing postdoctoral positions as a default (Schnoes et al, 2018), while having little to no negative impact on time to degree completion (Brandt et al, 2020;Lenzi et al, 2020;Schnoes et al, 2018) or research productivity as measured by publications (Brandt et al, 2020). Benefits for employers include a stronger talent pool (i.e., applicants who have sector knowledge, technical skills, and interpersonal skills).…”
Section: Introductionmentioning
confidence: 99%